The Paradigm of Islamic Science Amid the Artificial Intelligence Revolution: A Critical Examination of the Concepts of Science, Humanity, and Moral Responsibility in the Qur’an - Ade Adriani; Sudomo Sudomo; Mukmin Mukmin; Luthfiyah; Zuhrah Zuhrah (al-Afkar, Journal For Islamic Studies, 2026)
The artificial intelligence (AI) revolution presents urgent epistemological and ethical challenges to the Islamic science paradigm. This study aims to analyze the Qur'anic paradigm of 'ilm and its critical response to artificial intelligence, analyze the concept of human in the Qur'an towards artificial intelligence, and analyze the Qur'anic framework of moral responsibility as a normative basis for the use of artificial intelligence. The study uses a library research approach with a qualitative-descriptive analytical design, integrating content analysis and critical discourse analysis, and the maudhu'i interpretation method as a hermeneutical framework. Primary sources include the Qur'an, the book of tafsir Al-Misbah by M. Quraish Shihab, while secondary sources include academic literature indexed by Scopus, Web of Science, and the journal Sinta published in 2020-2025. The results show three main findings: first, the Qur'anic 'ilm paradigm positions AI only as an auxiliary instrument that is unable to reach the dimensions of hikmah, qalb, and ilmu ladunni. Second, the uniqueness of humans as al-insan, khalifah fi al-ardh, and 'abd Allah is ontological and irreducible to algorithmic systems. Third, the Qur'an provides a comprehensive normative framework for the use of AI through the principles of tawhid, 'adl, amanah, maslahah, shura, and reckoning. This research contributes to filling the academic gap by offering an integrative Qur'anic paradigm as an epistemological alternative in the global AI ethics discourse, which has been dominated by secular perspectives.